Cosmetic Body Lift. Issue 2 (February 2016) - Hamra, Sam T.; Small, Kevin H.
Abstract : Background: High-tension lateral abdominoplasty provides ideal central contouring of the abdomen, but it inadequately addresses laxity and fullness in the flank and lateral thigh. The adjunct of liposuction improves abdomen contour, but excess flank soft tissue often persists. Small case series in the literature have suggested an extended abdominoplasty to address these deficits with variable outcomes. The senior author (S.T.H.) reports his successes in the largest series to date of a 270-degree extended lipoabdominoplasty (cosmetic body lift) for non–massive weight loss patients to optimally contour the abdomen, hips, and flanks while lifting the lateral thigh and reducing thigh circumference. Methods: A retrospective chart review was conducted on patients who had a cosmetic body lift between 2004 and 2014. On average, outcomes were reviewed 1 year postoperatively. Results: From 2004 to 2014, 72 consecutive patients (one male patient) with an average age of 53 years (range, 33 to 73 years) had a cosmetic body lift. All patients were nonsmokers and had insignificant preoperative comorbidities. Average total liposuction volume was 3067 cc. Complications included seroma in 2.8 percent (two of 72), infection in 4.2 percent (three of 72), delayed wound healing in 5.6 percent (four of 72), necrosis/ischemia in 4.2 percent (three of 72), revision in 18.1 percent (13 of 72), and deep vein thrombosis in 1.4 percent (one of 72), with zero hematomas. Conclusions: This investigation is the largest series to date to evaluate the cosmetic body lift for the non–massive weight loss population. Consistent with reported complication rates of lipoabdominoplasty in the literature, the cosmetic body lift is a safe and effective operation for optimal waist contouring. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : Supplemental Digital Content is available in the text.